Higher levels of C-reactive protein in the acute phase of stroke indicate an increased risk for post-stroke depression: A systematic review and meta-analysis. (March 2022) - Yang, Yu; Zhu, Lijun; Zhang, Beilin; Gao, Jiguo; Zhao, Teng; Fang, Shaokuan
Highlights: Post-stroke depression is one of the most common neuropsychiatric disorders with high incidence and prevalence. Biomarkers for predicting post-stroke depression are required. A higher level of C-reactive protein in the acute phase of stroke indicates a higher risk for post-stroke depression. The level of C-reactive protein is a significant potential predictor of post-stroke depression. Abstract: Background: Investigations have revealed the association between inflammation and post-stroke depression (PSD). However, whether the C-reactive protein (CRP) level, a biomarker of inflammation, would affect the development of PSD is still controversial. Methods: A systematic search of databases was performed for eligible studies. Standardized Mean Difference (SMD) with 95 % Confidence Interval (CI) was used to assess the association between the CRP level in the acute phase of stroke and the risk of PSD. Results: 13 cohort studies that involved 3536 participants were included. Combined results showed that compared with non-PSD patients, the CRP level of PSD patients was significantly higher on admission (SMD = 0.19, 95 % CI: 0.12−0.27). A subgroup analysis by classifying the assessment time of depression showed obvious differences of the CRP levels between the PSD patients who were diagnosed more than 1 month after stroke and the non-PSD (1−3 months: SMD = 0.16, 95 % CI: 0.06−0.25; >3months: SMD = 0.34, 95 % CI: 0.18−0.51). Conclusion: A higher level of CRP in the acute phase of stroke suggests an increased risk for PSD.